Fowl Adenovirus Hepatitis (IBH and HHS): An Emerging Poultry Disease: VM263, 7/2024 - Butcher, Gary D.; Hossiny, Mohamed (EDIS, 2024)
The intended audience for this publication is commercial poultry producers and poultry veterinarians. This publication aims to provide an update and summary of fowl adenovirus hepatitis. Written by Gary D. Butcher and Mohamed Hossiny, and published by the UF College of Veterinary Medicine, UF/IFAS Extension, July 2024.